Forecast of Employment in Switzerland: The Macroeconomic View - Maitah, Mansoor; Toth, Daniel; Kuzmenko, Elena; Šréd, Karel; Řezbová, Helena; Šánová, Petra (International Journal of Economics and Financial Issues, 2016)
Switzerland is a unique in its own way country which, although being located in the heart of Europe, is an independent state and non EU member. Its political structure and future development direction is very different from the rest of the Europe. Swiss economy, in comparison with others neighboring EU countries, is much stronger. Being inspired by highly competitive and successful economic performance of Switzerland, the aim of the present study is to conduct a macroeconomic analysis via observing and forecasting the employment/unemployment rates in Switzerland. Employing time series analysis and econometric calculations own forecast will be collated with the forecast published by the Federal Statistical Office of Switzerland. The practical importance of the obtained results will be, as expected, manifested in finding possible ways how to fight unemployment and achieve at least 70% employment rate in the Czech Republic. Keywords: Switzerland, unemployment, employment, forecast. JEL Classifications: E2; R1; R100